The Effect of Organizational Culture and Work Motivation on Employee Performance at the Bengkulu City Education Office - Virdha Sapta Rini; Meiffa Herfianti; Yesi Indian Ariska (Penerbit Jurnal Indonesia, 2020)
The background that is taken into consideration in this research is that the organizational needs that are absolutely needed are the continued development of its human resources. Job performance or good work results by an employee in performing a task in accordance with the responsibilities assigned to him will affect the success of an organization. The sampling method used in this study was the Census, where the entire population became respondents, namely 126 employees of the Bengkulu City Education Office. The purpose of this study was to determine the effect of work organizational culture, work motivation on the performance of the employees of the Bengkulu City Education Office. The results showed that there was an influence of organizational culture on the performance of the Bengkulu City Education Office employees with the t test result of 0.324 (Sig. 0.01 <0.05) and there was an effect of work motivation on the performance of the Bengkulu City Education Office employee of 16.729 (Sig. 0, 04 <0.05). The simultas test results (together) prove that there is an influence of organizational culture and work motivation on the performance of the Benkulu City Education Office employees with an F test value of 139,958 (Sig. 0,000 <0.05). The coefficient of determination R2 is 0.695. A positive R2 value indicates that any increase in organizational culture and work motivation will have an impact on the performance of Bengkulu City Education Office employees. From the results of this study, it can be seen that the influence of the independent variable on the dependent variable. By looking at the results of the multiple coefficients, the influence given by the organizational culture variable, work motivation variable has a very positive and significant effect.